Bilateral Financial Linkages and Global Imbalances : A View on The Eve of the Financial Crisis - Milesi-Ferretti, Gian (IMF Working Papers; Working Paper ;, 2010)
We present a novel and comprehensive dataset of bilateral gross and net external positions in various financial instruments for the main advanced and emerging economies and regions, designed to improve our understanding of cross-border financial linkages. The data show no strong correspondence between country or region pairs with the largest gross versus net external positions, and the importance of international financial centers, including offshore centers, in intermediating financial flows. We also highlight some important data gaps in completing a network of cross-border holdings, related to the limited available information on the size and geographical pattern of external claims and liabilities of offshore centers, oil exporters, and other mostly emerging markets.